Relationship Between Waist Circumference and The Event of Andropause in Male Employees in Government Institutions of Badung Regency - Anak Agung Ayu Dian Indah Lestari; I Gusti Ngurah Pramesemara; Yukhi Kurniawan (Indonesian Andrology and Biomedical Journal, 2021)
Background: Andropause occurs with slow development and is a physiological process in males. Andropause symptoms arise vary in individuals. One of the factors that influence these symptoms is obesity, especially central obesity with a waist circumference of >90 cm. Objective: The purpose of this study is to show the relationship between waist circumference and the event of andropause. Methods: This research is an analytical study with a cross-sectional study approach conducted in one of the government institutions of Badung Regency, Bali Province. The sampling technique used was purposive sampling. The subjects consisted of 40 male employees at aged around 35-60 years. The research data were obtained from filling out the Androgen Deficiency in Aging Male (ADAM) score questionnaire and direct measurement of waist circumference. The statistical analysis used was the Chi-Square test. Results: The results showed that from 40 subjects, 23 (57.5%) subjects had a waist circumference of >90 cm, and a normal waist circumference of <90 cm in 17 (42.5%) subjects. There were 22 subjects (55.0%) who experienced andropause and 18 (45.0%) subjects who did not experience andropause. It was found that there was a significant relationship between waist circumference and the event of andropause among male employees in government institutions of Badung Regency (p = 0.001, OR = 11.7). Conclusion: The study has found that higher in waist circumference may contribute in the event of andropause. For further studies should takes a higher number of subjects to make it more accurate in wider population.